Formulation and Physicochemical Properties of Nanostructured Lipid Carriers from Beeswax and Rosemary oil as a Drug Carrier - Farhanim Mohd Latif (Science Faculty of Chiang Mai University, 2020)
The toxicity and insolubility of drugs in water remain a significant problem and has led to the development of food-grade drug delivery systems such as nanostructured lipid carriers (NLCs). A stable colloidal suspension of NLCs was prepared from a natural source of lipids. NLCs composed of beeswax (BW), rosemary oil (RO), and poloxamer 188 (P188) were prepared using melt-emulsification combined with ultrasonication. The optimised formulation with the smallest particle size and highest magnitude of zeta potential was selected for loading with terbinafine hydrochloride (TBHCl). TBHCl is a synthetic allylamine drug that functions as an antifungal. The optimised formulation comprised 3.75 % BW, 1.25 % RO, 3 % P188, and 92 % deionised water (DW). The mean particle size and zeta potential of the optimised NLCs was 174 ± 2 nm and -36 ± 5 mV, respectively. The morphology of the NLCs was observed as spherical with a dense appearance in the TEM images. The encapsulation and loading efficiencies were found to be dependent on the amount of TBHCl. The release of TBHCl from the optimised formulation was 62.87 ± 0.04 % during the 48-hour analysis.